1995
DOI: 10.1177/030089169508100209
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immunoassays for Tumor Markers CA 19-9, CA 15-3 and CA 125: Data from an International Quality Assessment Scheme

Abstract: Data collected in the 1993 and 1994 cycles of an international external quality assessment (EQA) program and in a national multicenter collaborative study were cumulatively analyzed to evaluate the standardization of the methods currently in use for the assay of mucinous tumor markers CA 19-9, CA 15-3 and CA 125. On average the between-laboratory variability was 15.2 and 16.0 CV% for CA 15-3 and CA 125 respectively; the between-laboratory variability found for CA 19-9 was markedly worse (mean 28.3 CV%). The va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Since all CA 15-3 assays utilize the same two monoclonal antibodies and the same standards, good agreement should be found with the different commercially available assays. Pilo et al 35 found good agreement (r = 0•98--0•99) between five different assays using control material. Furthermore, differences in concentrations between different kits were reported to be on average less than 10%.…”
Section: Agreement Between Different Assaysmentioning
confidence: 89%
See 2 more Smart Citations
“…Since all CA 15-3 assays utilize the same two monoclonal antibodies and the same standards, good agreement should be found with the different commercially available assays. Pilo et al 35 found good agreement (r = 0•98--0•99) between five different assays using control material. Furthermore, differences in concentrations between different kits were reported to be on average less than 10%.…”
Section: Agreement Between Different Assaysmentioning
confidence: 89%
“…Pilo et al 35 found good agreement (r = 0·98--0·99) between five different assays using control material. Furthermore, differences in concentrations between different kits were reported to be on average less than 10%.…”
Section: Agreement Between Different Assaysmentioning
confidence: 90%
See 1 more Smart Citation
“…However, this is partly counterbalanced by the large number of patients involved. It should be noted that the enrollment of cases with metastatic disease (many of them with heavy tumor load) may have facilitated agreement between laboratories and kits in assessing the supranormal CA 15-3 levels [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Blood is one such liquid that can easily be obtained to identify the presence of cancer [17] [18]. Several markers associated with cancer are analyzed in the blood, such as CA 15-3 for breast cancer, CA 19-9 for pancreatic, stomach and bile duct cancer, CA-125 for ovarian cancer, prostrate-specific antigen for prostate cancer and carcinoembryonic antigen for colorectal cancer [19]. However, these markers have limitations, the most important being their tendency to be detectable only when the tumor-burden is severe [20].…”
Section: Discussionmentioning
confidence: 99%